Trade‐Offs in Thin Film Solar Cells with Layered Chalcostibite Photovoltaic Absorbers. Issue 11 (25th January 2017) - Welch, Adam W.; Baranowski, Lauryn L.; Peng, Haowei; Hempel, Hannes; Eichberger, Rainer; Unold, Thomas; Lany, Stephan; Wolden, Colin; Zakutayev, Andriy
Abstract : Discovery of novel semiconducting materials is needed for solar energy conversion and other optoelectronic applications. However, emerging low‐dimensional solar absorbers often have unconventional crystal structures and unusual combinations of optical absorption and electrical transport properties, which considerably slows down the research and development progress. Here, the effect of stronger absorption and weaker carrier collection of 2D‐like absorber materials are studied using a high‐throughput combinatorial experimental approach, complemented by advanced characterization and computations. It is found that the photoexcited charge carrier collection in CuSbSe2 solar cells is enhanced by drift in an electric field, addressing a different absorption/collection balance. The resulting drift solar cells efficiency is <5% due to inherent J SC / V OC trade‐off, suggesting that improved carrier diffusion and better contacts are needed to further increase the CuSbSe2 performance. This study also illustrates the advantages of high‐throughput experimental methods for fast optimization of the optoelectronic devices based on emerging low‐dimensional semiconductor materials. Abstract : High‐throughput combinatorial experiments reveal current/voltage trade‐offs in chalcostibite (CuSbSe2 ) thin film solar cells. The stronger optical absorption and weaker electrical transport in this layered absorber material lead to drift‐dominated operation of the photovoltaic device approaching 5% efficiency. To further improve the efficiency, longer carrier diffusion and better electrical contacts are needed.